Les stratégies d’accompagnement vers l’autonomie : le cas d’une formation hybride de réorientation des néo-bacheliers à l’université - Dina Adinda; Pascal Marquet (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This paper discusses the mentoring strategies in blended learning program, which is adopted by teachers and is experienced by first year university students. The program studied in this research is mainly aims at developing students’ autonomy and is entitled. Researchers who were interested to the mentoring strategies of learning and its effects on students’ autonomy stated that teachers’ directive attitudes cannot facilitate students’ autonomy unless they implement as well a non-directive attitude, in order to help students in their learning. In this study, direct observations and interviews with teachers were performed. Data obtained from teachers are complemented by a questionnaire answered by students.The main finding suggests that most teachers adopt directive attitudes in teaching and that students believe that this attitude develops their autonomy. Results also reveal a difference from previous researches in face-to-face programs. The teachers’ attitudes in mentoring generate different effect from what has been observed up to now. Our work raises the issue of difference of mentoring attitudes effects, whether programs are delivered traditionally or the support of ICT.